2022
DOI: 10.1007/s00425-022-03864-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of petal transpiration in floral humidity generation

Abstract: Main conclusion Using petrolatum gel as an antitranspirant on the flowers of California poppy and giant bindweed, we show that transpiration provides a large contribution to floral humidity generation. Abstract Floral humidity, an area of elevated humidity in the headspace of flowers, is believed to be produced predominantly through a combination of evaporation of liquid nectar and transpirational water loss from the flower. However, the role of tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
(124 reference statements)
1
12
0
Order By: Relevance
“…As bee-pollinated flowers tend to hold higher sugar concentrations, diluted nectar is a likely deterrent indicating unfavorable rewards and so the perceived profitability of humid flowers will decrease ( Willmer 2011 ). In both instances, the mechanistic link between nectar and humidity ( von Arx 2013 , Harrap and Rands 2022 ) may provide the means by which transient profitability status is assessed. The effects of climate on pollinator preferences and reward status may mean that whilst in arid conditions a floral humidity signal encourages visitation and enhances learning responses towards humid flowers, the same signal in a humid environment may discourage visitation and inhibit floral humidity being learnt as a positive stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bee-pollinated flowers tend to hold higher sugar concentrations, diluted nectar is a likely deterrent indicating unfavorable rewards and so the perceived profitability of humid flowers will decrease ( Willmer 2011 ). In both instances, the mechanistic link between nectar and humidity ( von Arx 2013 , Harrap and Rands 2022 ) may provide the means by which transient profitability status is assessed. The effects of climate on pollinator preferences and reward status may mean that whilst in arid conditions a floral humidity signal encourages visitation and enhances learning responses towards humid flowers, the same signal in a humid environment may discourage visitation and inhibit floral humidity being learnt as a positive stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that flowers produce humidity that is elevated when compared to the immediate environment, having been demonstrated to occur in a number of flower species ( Corbet et al 1979 , von Arx et al 2012 , Nordström et al 2017 , Harrap et al 2020 ). Floral humidity is created by a combination of nectar evaporation and floral transpiration ( Corbet et al 1979 , Azad et al 2007 , von Arx et al 2012 , Harrap et al 2020 ) although the contribution of these two influences may vary between species, and appears to be different in its intensity from the humidity produced by nonfloral vegetation ( Harrap and Rands 2022 ). A sample of the floral headspace of 42 species found that 30 (71%) produce floral humidity of an intensity greater than would be expected from any conflating environmental humidity sources ( Harrap et al 2020 ).…”
mentioning
confidence: 99%
“…An alternative model to produce floral RH gradients is active gas exchange through floral stomata (a physiological mechanism), rather than (or complementary to) diffusion from nectar (a physical mechanism). To block the stomates of Datura flowers, petroleum jelly was smeared on the inner (adaxial) surface of the corolla as shown in fig1D (also see 35 ). These experiments were carried out in the following order.…”
Section: Floral Nectary and Stomate Blockage Experimentsmentioning
confidence: 99%
“…These results indicate that floral humidity is informative to pollinators, influencing their foraging decisions while suggesting that our view of floral RH as a biophysical consequence of nectar evaporation may be overly simplistic. Harrap and Rands 35 followed up their garden survey with manipulative experiments on two of their most humid flowers: Calystegia sylvatica and Escholtzia californica, yielding two important insights. First, funnel-shaped morning glory flowers produced the highest ΔRH values (~3.7%) indicating that floral shapes that enclose the headspace can retain higher humidity levels 31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation